Smith-Lemli-Opitz syndrome: clinical and biochemical findings in Brazilian patients - Scalco, Fernanda B. [UNESP] (2006)
Smith-Lemli-Opitz syndrome (SLOS) or RSH syndrome comprises multiple congenital anomalies and mental retardation. The underlying defect is a deficiency in the activity of delta7-sterol reductase, which decreases cholesterol and increases 7-dehydrocholesterol (7-DHC) levels. Our aim was to identify and evaluate the frequency of SLOS manifestations in a group of Brazilian patients. Based on our own data and those reported previously, we present a simple method that allows the estimation of probabilities favoring the diagnosis of SLOS. We evaluated 30 patients clinically and determined their plasma levels of cholesterol and 7-dehydrocholesterol. In 11 patients, the diagnosis was confirmed by ultraviolet spectrophotometry (UV). of 19 patients with normal laboratory results, 17 showed a high probability favoring the diagnosis of SLOS. The most significant signs and symptoms observed in over 2/3 of the biochemically confirmed cases were mental retardation (10/11), delayed neuropsychomotor development (10/11), syndactyly of 2nd/3rd toes (10/11), and craniofacial anomalies including microcephaly (11/11), incompletely rotated ears (8/11), palpebral ptosis (10/11), anteverted nostrils (10/11), and micrognathia (9/11). Genital anomalies were found in all male patients (6/6).